Epidemiology of injuries in National Collegiate Athletic Association men's football: 2014-2015 through 2018-2019 - Chandran, A.; Morris, S. N.; Powell, J. R.; Boltz, A. J.; Robison, H. J.; Collins, C. L. (Journal of Athletic Training, 2021)
Context: Football is among the most popular collegiate sports in the United States, and participation in National Collegiate Athletic Association (NCAA) football has risen in recent years. Background: Continued monitoring of football injuries is important for capturing the evolving burden of injuries in NCAA football. The purpose of this study was to describe the epidemiology of football-related injuries among men's NCAA football players during the 2014-2015 through 2018-2019 academic years. Methods: Exposure and injury data collected in the NCAA Injury Surveillance Program were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differential injury rates. Results: The overall injury rate was 9.31 per 1000 athlete-exposures. Most injuries occurred during general play (17.5%), blocking (15.8%), and tackling (14.0%). Concussions (7.5%), lateral ligament complex tears (6.9%), and hamstring tears (4.7%) were the most commonly reported injuries. Conclusions: Results of this study were generally consistent with previous findings, though changes over time in rates of commonly reported injuries warrant attention. Continued monitoring of injury incidence is needed to appraise the effectiveness of recently implemented rules changes.